(untitled) (Pedagogy of Higher and Secondary Education, 2009)
This article considers peculiarities of pedagogical practice organization of future Biology’s teachers, establishes its significance in ecological conscious forming. The author pays attention to pedagogical practice organization and its content’s pecularities.